Stylizacja na potoczność w przekładzie literatury czeskiej na język polski - Vítová, Lenka (Przekłady Literatur Słowiańskich, 2011)
Stylization of colloquial language in Polish translations of Czech literature Czech literature has traditionally made use of a distinctive stylization of colloquial language and dialect. This represents a significant challenge for translators into languages with less diverse stylistics as they seek to find a mode of capturing the original’s emotionality. This article explores translators’ strategies when dealing with this problem and uses examples of works by Jaroslav Hašek, Bohumil Hrabal, Jáchym Topol and Irena Dousková who stylize colloquial language in a variety of ways. The author uses a comparative analysis of the original and the translation to determine how and to what extent the individual translators achieved an adequate rendering of the original. The translators in question are Paweł Hulka-Laskowski, Józef Waczków and Antoni Kroh in the case of Hašek; Andrzej Czcibor-Piotrowski, Jan Stachowski and Piotr Godlewski in the case of Hrabal; Leszek Engelking in the case of Topol and Joanna Derdowska in the case of Dousková. In the conclusion the author suggests four categories of stylization of colloquial language (depending on its form and aim): folk (Hašek), aestheticizing (Hrabal), naturalist (Topol) and humorous (Dousková). She also argues that it is increasingly more important to provide as accurate a translation as possible of all the aspects of the text, including those that differ from the national tradition. This is in line with the latest trends when translations incorporate increasingly more of the Other and are characterized by a significant shift from adaptation (viewed through the national prism) to exoticization (viewing one’s home through the lenses of the whole world).